Arsip Sebagai Bukti Hukum Dalam Isu Kasus Dugaan Pemalsuan Ijazah Presiden Joko Widodo - Meilani, Najwaa Sheva; Miswendi, Raniah; Fashihah, Jihan; Safitri, Wulan Amelia; Irfaan, Hasani Zul; Razaq, Muhammad Mas Ar; Nhizam, Aan Hariel (Brand Communication, 2025)
This study aims to analyze the role of document and archival legality in shaping public opinion, emphasizing the significance of archives as valuable assets and legal evidence. The focus is placed on the case involving allegations of diploma forgery against the former President of the Republic of Indonesia, Joko Widodo. The research aims to provide insight into how archives can serve as legitimate legal evidence and to encourage the public to understand and apply proper archival management as part of legal and information literacy. The research employs a qualitative approach using content analysis with analytical parameters. Data sources from public comments on instagram and any legal documents. The findings reveal that the Indonesian National Police’s Criminal Investigation Agency (Bareskrim Polri) declared President Joko Widodo’s diploma authentic and valid following both physical and digital verification of academic documents. Universitas Gadjah Mada (UGM) also confirmed the diploma’s legitimacy. Digital archives, such as theses and academic administration records, served to reinforce this evidence. Public response to the case based on social media analysis showed a majority of negative sentiment (50%), followed by neutral (35%) and positive (15%) reactions. The low level of archival literacy contributed to public susceptibility to disinformation, with perceptions more influenced by the public image of the figure rather than legal or archival procedures.